Individual health passport storage, sharing and verification scheme based on blockchain - GAO Hancheng; JI Haoyu; GAO Chenhao; HUANG Haiping (网络与信息安全学报)
As the demand for international travel escalates, the individual health passport has emerged as an essential instrument for verifying the health status of travelers and fulfilling entry criteria. To tackle the challenges associated with the global sharing of individual health passports, including information fragmentation, privacy concerns, and the risk of counterfeiting, a blockchain-based scheme for the secure storage, sharing, and verification of individual health passports was developed. This scheme employed a hybrid on-chain and off-chain storage methodology and incorporated searchable encryption with blockchain technology. This integration aimed to streamline blockchain storage, alleviating the storage load while guaranteeing the dependable archiving and secure dissemination of user-sensitive data. The scheme also refined the weak consensus mechanism, with an improved algorithm that achieved consensus in merely two stages. This innovation significantly diminished the communication complexity among nodes and amplified the throughput capacity of the blockchain system. To cater to multi-user environments, the scheme introduced and enhanced aggregate signature technology. This enhancement minimized the computational load associated with signature verification and facilitated the swift identification of potential malicious forgers. An exhaustive security analysis was conducted to substantiate the scheme's security and dependability. Subsequent simulation outcomes indicate that, in comparison to existing solutions, the proposed scheme realizes substantial optimizations of up to 49.89% in computational overhead and 25.81% in communication overhead within multi-user contexts. Moreover, the proposed consensus mechanism demonstrates significant efficiency benefits across varying node counts.